Host-functionalization of macrin nanoparticles to enable drug loading and control tumor-associated macrophage phenotype - Sarkar, Biplab; Arlauckas, Sean P.; Cuccarese, Michael F.; Garris, Christopher S.; Weissleder, Ralph; Rodell, Christopher B. (Frontiers in Immunology, 2024)
Macrophages are critical regulators of the tumor microenvironment and often present an immunosuppressive phenotype, supporting tumor growth and immune evasion. Promoting a robust proinflammatory phenotype has emerged as a therapeutic modality that supports tumor clearance, including through synergy with immune checkpoint therapies. Polyglucose nanoparticles (macrins), which possess high macrophage affinity, are useful vehicles for delivering drugs to macrophages, potentially altering their phenotype. Here, we examine the potential of functionalized macrins, synthesized by crosslinking carboxymethyl dextran with L-lysine, as effective carriers of immunostimulatory drugs to tumor-associated macrophages (TAMs). Azide groups incorporated during particle synthesis provided a handle for click-coupling of propargyl-modified β-cyclodextrin to macrins under mild conditions. Fluorescence-based competitive binding assays revealed the ability of β-cyclodextrin to non-covalently bind to hydrophobic immuno-stimulatory drug candidates (Keq ~ 10 3 M -1 ), enabling nanoparticle drug loading. Furthermore, transcriptional profiles of macrophages indicated robust pro-inflammatory reprogramming (elevated Nos2 and Il12; suppressed Arg1 and Mrc1 expression levels) for a subset of these immuno-stimulatory agents (UNC2025 and R848). Loading of R848 into the modified macrins improved the drug's effect on primary murine macrophages by threefold in vitro. Intravital microscopy in IL-12-eYFP reporter mice (24 h post-injection) revealed a twofold enhancement in mean YFP fluorescence intensity in macrophages targeted with R848-loaded macrins, relative to vehicle controls, validating the desired pro-inflammatory reprogramming of TAMs in vivo by cell-targeted drug delivery. Finally, in an intradermal MC38 tumor model, cyclodextrinmodified macrin NPs loaded with immunostimulatory drugs significantly reduced tumor growth. Therefore, efficient and effective repolarization of tumor-associated macrophages to an M1-like phenotype-via drug-loaded macrins-inhibits tumor growth and may be useful as an adjuvant to existing immune checkpoint therapies.